Respostas
respondido por:
1
Y = ax+ b
I) A(5,4) x= 5 e y =4
4 = 5a +b
II) B(7,6) x = 7 e y = 6
6 = 7a +b
III) Sistema :
5a + b = 4 *(-1) -----> -5a - b = - 4
7a +b = 6
--------------------
2a + 0 = 2
a =![\frac{2}{2} =1 \frac{2}{2} =1](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B2%7D+%3D1)
IV) Substitui em qualquer uma das equações para encontrar o valor de b :
7a +b =6
7.1 + b = 6
b = 6 -7
b = - 1
V) y = ax +b
y = x - 1
x - y -1 = 0
I) A(5,4) x= 5 e y =4
4 = 5a +b
II) B(7,6) x = 7 e y = 6
6 = 7a +b
III) Sistema :
5a + b = 4 *(-1) -----> -5a - b = - 4
7a +b = 6
--------------------
2a + 0 = 2
a =
IV) Substitui em qualquer uma das equações para encontrar o valor de b :
7a +b =6
7.1 + b = 6
b = 6 -7
b = - 1
V) y = ax +b
y = x - 1
x - y -1 = 0
douglascristian:
obrigado mas nao tem nenhuma destas opçoes aqui.
x-y+1=0
x-y-1=0
x+y-1=0
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás